Soreness and ulcers 1: recurrent ulcers due to aphthae and aphthous-like ulcers - Farah, Camile (Henry Stewart Talks, 2017)
General causes of oral ulceration, Recurrent Aphthous Stomatitis (RAS) clinical presentation & classification, RAS etiology & pathogenesis, RAS treatment & referral, Aphthous-associated conditions including Crohn's disease & Celiac disease, Aphthous-like lesions including herpetic ulcers & erythema multiforme